2017
DOI: 10.2495/978-1-78466-249-3/010
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion of mild steel and 316L austenitic stainless steel with different surface roughness in sodium chloride saline solutions

Abstract: The corrosion behaviour of mild steel and 316L austenitic stainless steel was investigated in saline solution containing 1 and 3% NaCl. Specimens with surface roughness of 200, 600 grit emery paper and 1 μm diamond paste were investigated. The anodic polarization measurement technique was performed at a scan rate of 1 mV/s for a fixed period of 1 hour. Experimental results revealed that chloride ions have a significant effect on the corrosion behaviour of both steels as expected. As the surface roughness of 31… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
7
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 8 publications
4
7
0
4
Order By: Relevance
“…This can be attributed to the high rate of corrosion propagation after initiation. It is said that localized corrosion is controlled by the diffusion process and in this case once the corrosion started, it propagated at a fast rate due to the continuous diffusion process and the formation of acid media at the bottom of the grooves [8]. The results are in a good agreement with the observations of Alvarez on AE44 magnesium alloy which has similar characteristics as mild steel i.e.…”
Section: Discussionsupporting
confidence: 81%
See 4 more Smart Citations
“…This can be attributed to the high rate of corrosion propagation after initiation. It is said that localized corrosion is controlled by the diffusion process and in this case once the corrosion started, it propagated at a fast rate due to the continuous diffusion process and the formation of acid media at the bottom of the grooves [8]. The results are in a good agreement with the observations of Alvarez on AE44 magnesium alloy which has similar characteristics as mild steel i.e.…”
Section: Discussionsupporting
confidence: 81%
“…Alvarez et al [9] showed that the corrosion rate in AE44 from polished coupons (with lower roughness) was notably greater than the corrosion rate from the semi-polished coupons (with higher roughness). Similar behaviour was observed by Abosrra et al [8] on mild steel in saline solution containing 1 and 3% NaCl. In his work Abosrra et al [8] showed that the improvement of the surface finish led to a shift in the corrosion potential to more noble states and to an increase of the corrosion rate.…”
Section: Introductionsupporting
confidence: 74%
See 3 more Smart Citations